ANALIZA UMIEJĘTNOŚCI REFLEKSYJNYCH PRZYSZŁYCH NAUCZYCIELI JĘZYKA ANGIELSKIEGO - Czajka, Ewa (Neofilolog, 2019)
The fact that a successful language instructor has to be a reflective practitioner is undeniable. However, observations made during teacher training courses reveal trainees’ reluctance to self-evaluate their conduct and poorly-developed reflective thinking skills. In an attempt to aid the future teachers’ progress in this area, a series of written tasks was introduced during a course. These included: self-evaluation of one’s strengths and weaknesses, pre and post-microteaching reflections. The analysis of these narratives provides an insight into the trainees’ self-evaluation processes and demonstrates a gradual progress in their abilities from descriptive to productive reflective thinking. Thus the results seem to confirm the positive influence of the intervention.